2012
DOI: 10.3109/09553002.2012.702299
|View full text |Cite
|
Sign up to set email alerts
|

Dominant negative Ubiquitin-conjugating enzyme E2C sensitizes cervical cancer cells to radiation

Abstract: These results suggested that the Ubiquitin-conjugating enzyme E2C (UBE2C) gene is a potential therapeutic target for cervical cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Abundant experimental evidence has shown a role for Ube2c in human tumor initiation and progression. On the other hand, there are very few reports that implicate Ube2c in DNA damage response to radiation [49, 50]. Moreover, the mechanistic details of Ube2c response to radiation, as well as their pathophysiological significance remain unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Abundant experimental evidence has shown a role for Ube2c in human tumor initiation and progression. On the other hand, there are very few reports that implicate Ube2c in DNA damage response to radiation [49, 50]. Moreover, the mechanistic details of Ube2c response to radiation, as well as their pathophysiological significance remain unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Cells overexpressing UBE2C ignore the mitotic spindle checkpoint signals and lose genomic stability, which leads to cancer and poor prognosis in many cancers. Our previous studies have shown UBE2C to be a potential target for treatment in cervical cancer [8ā€“10]. …”
Section: Discussionmentioning
confidence: 99%
“…We have also shown that a 7 gene signature which includes UBE2C could be useful to identify patients who can be treated with radiotherapy alone [9]. Functional studies inhibiting UBE2C was found to enhance radiation and chemo-sensitivity in cervical cancer cell lines [10]. UBE2C has been shown to be preferentially over expressed in cancers compared to 17 other E2 genes [7].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that UBE2C aberrant UbcH10 expression leads to chromosomal instability and further indicate UBE2C is a potential trigger for the initiation of cancer. Substantial evidence has showed abnormal high UBE2C was observed in various human solid cancers including esophageal adenocarcinoma, thyroid cancer, colon cancer, ovarian cancer, breast cancer, hepatocellular carcinoma, and cervix cancer (pallante et al, 2005;Lin et al, 2006;Berlingieri et al, 2007a;2007b;Ieta et al, 2007;Chen et al, 2010;Bose et al, 2012). In colorectal cancer cells, Bavi et al found UBE2C overexpression promoted cellular proliferation, whereas depletion of UBE2C expression suppressed growth of cells (Bavi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%